Teachers’ perceptions, attitudes and knowledge of online learning for students with disabilities in Saudi Arabia - Aldousari, Ahmed; Yuan, Weili (Journal of Education and e-Learning Research, 2024)
This study investigates how Saudi Arabian special education teachers believe about online learning for students with disabilities evaluating their familiarity with the subject and identifying factors affecting their preparedness to adopt this mode of instruction. Researchers aim to understand educators’ perceptions of delivering special education through online platforms in Saudi Arabia through a cross-sectional analysis of quantitative data complemented by responses to three open-ended questions. The study involves 130 in-service special education teachers currently employing online methods to teach students with disabilities. The research findings reveal key insights: Firstly, most participants (79%) viewed online learning as beneficial for their students, echoing prior research highlighting its feasibility for students with disabilities. Secondly, many teachers indicated gaps in their knowledge (34%) and confidence (31%) related to online instruction emphasizing the need for tailored professional development. Lastly, challenges related to internet access (36%) and software availability (35%) underline infrastructure barriers requiring attention to facilitate effective online education for individuals with disabilities in Saudi Arabia. These findings underscore the importance of ongoing professional development and infrastructure enhancements to optimize the online learning experience in Saudi Arabia. This paper concludes by outlining practical implications and suggesting avenues for future research.